Teaching Academic Listening through Metacognitive Instruction Viewed from Students’ Interest - Asman, Hamid (JET ADI BUANA, 2016)
This experimental study was carried out at the English Education Department of IKIP-PGRI Pontianak in the Academic Year of 2015/2016. The population was the third semester students and the sample consisted of two classes. The experimental group was treated by using metacognitive instruction; while the control group was treated by using Cognitive instruction. The sampling technique used was cluster random sampling. The instruments used to collect the data were questionnaire and listening test. The data were analyzed by using multifactor analysis of variance (ANOVA 2X2) and tukey test. The findings were: (1) metacognitive instruction was more effective than Cognitive instruction to teach academic listening; (2) the students with high listening interest have better ability; and (3) there was an interaction between teaching instruction and students’ interest. It can be concluded that metacognitive instruction is an effective way to teach academic listening